A política de municipalização do ensino: da teoria à prática - Sousa, Elizabeth Coelho de (1999)
This dissertation presents, as its main .goal, the analysis of council sponsoring education in Brazil since 1828, when our first district councils were instituted in each empire village. The analysis incorporates principies and concepts, which are within the laws that register the main Brazilian education directives. It takes as theoretical reference the historical structural conception through analytical political and social educational categories, aspects related to power transferring, distribution of financial resources, and good standard education. We analysed relations stated between federal government, state government and city council, considering taking off the central core action as a criteria of sharing competence and duties that should add efforts to provide council sponsoring education. We discuss the history of council sponsoring education in Uberlândia, Minas Gerais, and investigated it according to how speech and practice occurred during the period between 1997 and 1999. The research presents a bibliographic survey, document analysis and questionnaires answered by administrators, specialists, and teachers from state schools as well as from council sponsoring schools, who were somehow evolved with the council sponsoring school implementing process of Uberlândia's state schools. We are for a council sponsoring education institutionalisation which should occur, gradually, within the organised society and public power.